An Evaluation of the Correlation between Hepcidin Serum Levels and Disease Activity in Inflammatory Bowel Disease - Paköz, Zehra Betül (Gastroenterol Res Pract, 2015)
Aim. While there are many well-defined serological markers for inflammatory bowel disease (IBD), there is limited evidence that they positively affect clinical outcomes. This study aimed to evaluate the correlation between hepcidin serum levels and disease activity in IBD. Materials and Methods. Eighty-five consecutive IBD patients were enrolled in the study. Hepcidin serum levels were assessed using an enzyme-linked immunosorbent assay (ELISA) and were compared with disease activity as well as the interleukin-6 (IL-6) and C-reactive protein (CRP) levels. Results. The mean hepcidin serum levels in Crohn's disease (CD) patients in remission and in the active phase were 3837 ± 1436 and 3752 ± 1274 pg/mL, respectively (P = 0.613). The mean hepcidin serum levels in ulcerative colitis (UC) patients in remission and in the active phase were 4285 ± 8623 and 3727 ± 1176 pg/mL, respectively (P = 0.241). Correlation analysis between inflammatory markers and hepcidin serum levels indicated that there was no correlation between hepcidin levels and IL-6 (P = 0.582) or CRP (P = 0.783). Conclusion. As an acute-phase protein, hepcidin seems to have a lower efficacy than other parameters in the detection of activation in IBD.